The Effectiveness of KIP-Kuliah Scholarships on Student Academic Achievement in NTT Province: A Dual-Process Theory Approach to Financial Behavior and Social Environment - Marianus Hendrilensio Sanga; Resvina Situmorang; Katarina Derice Hale (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
Financial behavior of the KIP-Kuliah scholarship is a critical factor in supporting students’ academic success. This study examines dual-process thinking: intuition (Type 1) and rationality (Type 2), and the effectiveness of the KIP-Kuliah scholarship in shaping students’ financial behavior and academic achievement. Using a mixed-methods approach, the study integrates quantitative analysis through Structural Equation Modeling–Partial Least Squares (SEM-PLS) with qualitative interviews to enrich the interpretation of the findings. The results indicate that the KIP-Kuliah scholarship significantly improves academic achievement and encourages more structured financial behavior, with rational decision-making exerting a stronger influence than intuition. However, financial behavior does not mediate the relationship between scholarship effectiveness and academic performance, and the social environment does not moderate the effect of dual-process thinking on financial behavior. The study concludes that the scholarship directly enhances academic outcomes, while rational cognitive processes remain key to effective financial behavior.